Intestinal Obstructions 2020
DOI: 10.5772/intechopen.91311
|View full text |Cite
|
Sign up to set email alerts
|

Caecal Volvulus

Abstract: Colonic volvulus is the third leading cause of large bowel obstruction. About 35% of these are located in the caecum. Though, relatively, a rare cause of obstruction, the incidence of caecal volvulus is steadily increasing at a rate of about 5% per year. Mortality due to caecal volvulus may be as high as 40% especially in the presence of gangrene and sepsis. Clinical presentation may be acute and fulminant or as a mobile caecum syndrome with intermittent abdominal pain. "Whirl," "Coffee bean," and "bird beak" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
3
2
Order By: Relevance
“…The male predominance in our study was comparable to that of Kaboré RAF et al [8] who reported a sex ratio of 2.9. On the other hand, our results were superior to those of Kambiré JL et al [5] at the Ouahigouya regional university hospital in Burkina Faso and Haridimos M et al [14] at the University of technology teaching hospital in Nigeria who found a sex ratio of 1.8 and 1.1. Our results were lower than those of Harouna Y et al [7] at Zinder National Hospital in Niger who found a sex ratio of 5.2.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The male predominance in our study was comparable to that of Kaboré RAF et al [8] who reported a sex ratio of 2.9. On the other hand, our results were superior to those of Kambiré JL et al [5] at the Ouahigouya regional university hospital in Burkina Faso and Haridimos M et al [14] at the University of technology teaching hospital in Nigeria who found a sex ratio of 1.8 and 1.1. Our results were lower than those of Harouna Y et al [7] at Zinder National Hospital in Niger who found a sex ratio of 5.2.…”
Section: Discussioncontrasting
confidence: 84%
“…Small bowel obstructions were more frequent compared to colonic occlusions in our study. Our results were superior to those of Shimou I et al [9] in Morocco who reported a rate of 54.36%, but were comparable to those of Haridimos M et al [14] in Nigeria who noted 76% of cases of hail occlusions versus 24% of colonic occlusions. The loop was viable in most cases in our study, as found by Harissou A et al [1] which recorded 69.6% of cases.…”
Section: Discussioncontrasting
confidence: 53%
“…Cecal volvulus can occur due to other factors such as intestinal bands/adhesions, tumor, pregnancy, long mesentery, abdominal or pelvic mass, abdominal injury, large bowel obstruction, psychological disorders, sedentary lifestyle, mega-colon, and chronic constipation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CT scan may show signs of ischemia or gut perforation, such as pneumoatosis intestinalis or pneumoperitoneum [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Definitive treatment should be sought as soon as the patient has been adequately resuscitated, Initial management entails conservative measures such as analgesia, antiemetics, intravenous fluids, having the patient stop any oral intake, insertion of a nasogastric tube to facilitate proximal bowel decompression, and insertion of a urinary catheter to monitor fluid input/output [ 13 ].…”
Section: Discussionmentioning
confidence: 99%